Pengaruh Penerapan Metode Pembelajaran Blended Learning Terhadap Motivasi Belajar Pada Mata Pelajaran Ekonomi di SMA Negeri 20 Pangkep - Rahmatullah, Rahmatullah; Sahrul Ramadhan; Inanna; Nurjannah; Tahir, Thamrin (Universitas Pendidikan Ganesha, 2022)
This study aims to determine and analyze the effect of applying blended learning on students' learning motivation in economics subjects at SMA Negeri 20 Pangkep. The research method in this research is quantitative method, and the data collection method in this study is through observation, documentation and questionnaires or questionnaires. The number of samples in this study were 95 from 129 students majoring in Social Sciences with grade X and grade IX at SMA Negeri 20 Pangkep and then analyzed using simple linear regression analysis. Based on the results of the study, it shows that there is a significant influence in the application of the blended learning on students' learning motivation in economic subjects at SMA Negeri 20 Pangkep. The simple linear regression equation shows the effect of the application of the blended learning learning method on students' learning motivation in economic subjects at SMA Negeri 20 Pangkep has a positive influence, and the magnitude of the influence of the application blended learning on students' learning motivation in economics subjects in SMA Negeri 20 Pangkep, amounted to 41.1% while 58.4% was influenced by other factors.